Antioxidant activity profile of extract and fraction of kersen (Muntingia calabura L.) fruits prepared by different methods. Issue 1 (February 2022) - Nur, S; Aswad, M; Yulianti, R; Sami, F J; Burhan, A; Fadri, A; Khairi, N; Nursamsiar,
Abstract: The public widely uses kersen ( Muntingia calabura L) fruit for consumption and treatment because Kersen fruit has various vitamins, minerals, and secondary metabolite compounds that reduce free radicals. The purpose of this study was to see the effectiveness of kersen fruit as an antioxidant agent. In this study, the samples used were ethanol extract (EE), Aqueous ethanol fraction (EF), ethyl acetate fraction (EAF), and n-hexane (HF) fraction from kersen fruit ( Muntingia calabura L). The samples were evaluated by observing the antioxidant activity profile using various methods, i.e., nitric oxide, β-carotene bleaching assay, hydroxyl radicals, and iron chelating. The results of this study showed that the IC50 values of EE (31.05 μg/mL), AEF (33.86 μg/mL), FEA (40.48 μg/ml) gave powerful antioxidant activity while HF showed weak results (459 μg/ml). In the nitric oxide method. The hydroxyl radical method with IC50 values of 32.06 μg/mL (EE), 38.73 μg/mL (EF), 22.18 μg/mL (EAF) gave very strong activity, and 53.37 μg/mL (HF) with strong activity. The β-carotene bleaching method gave powerful antioxidant activity results with IC50 values <50 μg/mL in each sample. The Iron Chelation method showed weak antioxidant activity (IC50 > 200 μg/mL) of each sample. Based on the results obtained, it can be concluded that the antioxidant activity of extracts and fractions in kersen fruit has a different activity profile according to the test method used.